GACHA: an Islamic study on the element of Gambling (Maisir) and uncertainty (Gharar) in micro-transaction - Mohd Kifly, Muhammad Khairul Iman; Mat Jubri@Shamsuddin, Mustafa (2022)
The purpose of this research is mainly to discuss the Islamic ruling deduction on the issue of GACHA micro-transaction by taking into account forbidden transactional elements like gambling (maisir) and uncertainty (gharar). GACHA, also known as a game-of-chance, is one of the newer monetization mechanics adopted by video games developer and its implementation can be witnessed in various digital games. Through this, players may acquire virtual items, albeit ambiguously, and this uncertain nature will profit the developers massively. Thus, this research aims to provide clarity on the definition of GACHA, by studying its attributes and features through past studies and theses. Additionally, this research will examine the characteristics of gambling (maisir) and uncertainty (gharar), which is extremely important when it comes to the comprehension of the ruling deduction provided by Islamic scholars and contemporary Fatwa. Additionally, the researchers will also attempt to study the reality of GACHA in today’s world, such as the shapes and forms of GACHA, and its significant impact on society backed by pieces of evidence from recent years. Thus, the research method that has been used for this research is the qualitative method which is a library method, and an analytical review of the gathered data. It was established that the Islamic rulings on GACHA are that it is impermissible to be practised as it involves forbidden transactional elements.